Ionization-induced tautomerization in cytosine and effect of solvation - Das, Tamal; Ghosh, Debashree (Journal of Physical Chemistry A, 2014)
The recent observation of excitation-induced tautomerization in gas-phase cytosine motivated us to investigate the possibility of facile tautomerization in ionized cytosine and the effect of solvation on the tautomerization barriers. The tautomerization mechanisms were characterized at the density functional theory (DFT)omega B97X-D and coupled-cluster singles and doubles (CCSD) levels of theory. Vertical and adiabatic ionization energies (VIEs and AIEs, respectively) of the tautomers of cytosine and the microsolvated species were calculated with the equation-of-motion ionization-potential coupled-cluster (EOM-IP-CCSD) method. We observed that, in microsolvated cytosine, the solvatochromic shifts of the VIEs can be both blue- and red-shifted depending on the tautomers. This is explained by the analysis of the charge dipole interactions between the cytosine and water molecules. We noticed that, upon ionization, gas-phase tautomerization barriers are reduced by 0-4 kcal/mol, whereas microsolvated (with one water) tautomerization barriers are reduced by 4-5 kcal/mol. We also investigated the tautomerization process in solvation using a continuum model with one active water molecule in the quantum mechanical region. We noticed that, even though bulk solvation has a significant effect on ionization energies, its effect on the ionization-induced tautomerization barrier is minimal.

Intramolecular dehydrogenative coupling of 2,3-diaryl acrylic compounds: access to substituted phenanthrenes - Gupta, Vijay; Rao, V. U. Bhaskara; Das, Tamal; Vanka, Kumar; Singh, Ravi P. (Journal of Organic Chemistry, 2016)
A simple, facile, and environmentally benign intramolecular dehydrogenative coupling of various 1,2-diarylethylenes for the synthesis of phenanthrenes in excellent yield has been described. This new methodology uses ceric ammonium nitrate (CAN) as a promoter at room temperature and has been extended to intermolecular synthesis of biaryl compounds. The electron transfer from methoxyarene to cerium leads to cationic radical formation, which further proceeds to intramolecular coupling. Preliminary mechanistic investigation by EPR spectroscopy and density functional theory calculation suggested a similar view.

Insights into the origin of life: did it begin from HCN and H2O? - Das, Tamal; Ghule, Siddharth; Vanka, Kumar (Acs Central Science, 2019)
The seminal Urey-Miller experiments showed that molecules crucial to life such as HCN could have formed in the reducing atmosphere of the Hadean Earth and then dissolved in the oceans. Subsequent proponents of the "RNA World" hypothesis have shown aqueous HCN to be the starting point for the formation of the precursors of RNA and proteins. However, the conditions of early Earth suggest that aqueous HCN would have had to react under a significant number of constraints. Therefore, given the limiting conditions, could RNA and protein precursors still have formed from aqueous HCN? If so, what mechanistic routes would have been followed? The current computational study, with the aid of the ab initio nanoreactor (AINR), a powerful new tool in computational chemistry, addresses these crucial questions. Gratifyingly, not only do the results from the AINR approach show that aqueous HCN could indeed have been the source of RNA and protein precursors, but they also indicate that just the interaction of HCN with water would have sufficed to begin a series of reactions leading to the precursors. The current work therefore provides important missing links in the story of prebiotic chemistry and charts the road from aqueous HCN to the precursors of RNA and proteins.

Insights into chemical reactions at the beginning of the universe: from HeH+ to H-3 (+) - Dash, Soumya Ranjan; Das, Tamal; Vanka, Kumar (Frontiers in Chemistry, 2021)
At the dawn of the Universe, the ions of the light elements produced in the Big Bang nucleosynthesis recombined with each other. In our present study, we have tried to mimic the conditions in the early Universe to show how the recombination process would have led to the formation of the first ever formed diatomic species of the Universe: HeH+, as well as the subsequent processes that would have led to the formation of the simplest triatomic species: H-3 (+). We have also studied some special cases: higher positive charge with fewer number of hydrogen atoms in a dense atmosphere, and the formation of unusual and interesting linear, dicationic He chains beginning from light elements He and H in a positively charged atmosphere. For all the simulations, the ab initio nanoreactor (AINR) dynamics method has been employed.
Keywords: ab initio molecular dynamics; ab initio nanoreactor; Density functional theory; origin of molecules in the universe; the earliest lewis acid